2019
DOI: 10.1177/0959683619883011
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the summer Asian westerly jet over the last millennium based on the PMIP3 simulations

Abstract: Investigation of the evolution of summer Asian westerly jet (AWJ) in Earth history may deepen our understanding of the behavior of AWJ in the present and future. Here, the variation of summer westerlies and the associated mechanisms over West and East Asia are examined using the last millennium simulations from the Paleoclimate Modeling Intercomparison Project Phase III (PMIP3). The multimodel ensemble mean of 11 PMIP3 models reproduces the spatial distribution of modern zonal wind at 200 hPa and captures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Model‐based studies have shown that the summer STJ over the larger Asian domain moved generally poleward during the Medieval Climate Anomaly due to a combination of several factors including an El Niño‐like Pacific Ocean, warm Indian Ocean, large volcanic eruptions, and higher solar irradiance (Fallah et al, 2016; Jiang et al, 2020). Our multicentury HJL proxy could be used as a real‐world target to compare against long model simulations and thereby determine whether the enhanced variance and recent spate of poleward excursions is in fact unusual and due to either natural climate variability or anthropogenic climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Model‐based studies have shown that the summer STJ over the larger Asian domain moved generally poleward during the Medieval Climate Anomaly due to a combination of several factors including an El Niño‐like Pacific Ocean, warm Indian Ocean, large volcanic eruptions, and higher solar irradiance (Fallah et al, 2016; Jiang et al, 2020). Our multicentury HJL proxy could be used as a real‐world target to compare against long model simulations and thereby determine whether the enhanced variance and recent spate of poleward excursions is in fact unusual and due to either natural climate variability or anthropogenic climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the impact of PDO on the ECSP is more prominent than that of the AMO under the warmer background from the perspective of the last millennium. On the one hand, the meridional temperature gradient reduction during the MCA can cause the poleward movement of the westerly jet stream compared to that during the LIA (Jiang, Yan, & Wang, 2020). Then, the stream is located more northward and only affects the precipitation north of the YRV.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Meanwhile, earlier research was mainly focused on decadal climate change in the globe/NH (Schurer et al ., 2014; Atwood et al ., 2016) and in Europe (Hegerl et al ., 2011; Luterbacher et al ., 2016). In previous research based on the simulations participated in PMIP3, there are many studies on regional moist (Shi et al ., 2016a; Bai et al ., 2019) and monsoon (Sun et al ., 2015; Shi et al ., 2016b; Shi et al ., 2017; Jiang et al ., 2020) climate change in China during the LM, while regional SAT attribution has received less attention. A previous study showed that summer SAT decreased over time during the LM, with multi‐decadal variations superimposed on the long‐term cooling.…”
Section: Introductionmentioning
confidence: 99%